Prioritization of Factors Influencing Safety Performance on Construction Sites: A Study Based on Grade Seven (G7) Main Contractors' Perspectives - Lee, Chia Kuang; Yusmin, Jaafar (2013)
Construction industry is one of the major industries that propels Malaysia's economy. Although the construction industry itself highly contributes to our nation's GDP growth, yet the high fatality rates on construction sites have caused grave concern among safety practitioners and the stakeholders. The aim of this study was to identify and prioritize the degree of importance of the factors that influence the safety performance on construction sites as perceived by the contractors on sites. A survey which took the form of a questionnaire was administered to 110 major construction companies in Malaysia to implore the safety factors from Grade Seven (G-7) Main contractors. About 63 main contractors participated in this survey, which achieved a high response rate of 61%. This study prioritized the factors by using relative importance indices (I). The result revealed that the most important major factor was (1) Management Activities on Site, followed by (2) Personnel, (3) Process, (4) Policy, (5) Technical, and (6) Incentives.; while the top three most important factor elements were (1) Safety Inspection, (2) On site and HQ Management attitude towards safety, and (3) Safety Regulation Enforcement. Accordingly, this study prescribed several suggestions on the prioritized factor elements specifically as means of managing safety on sites proactively, taking the industry towards zero accident and strive for better improvements.